Contemporary Peacemaking
XVII, 401 p.
Keywords: Contemporary Peacemaking draws on recent experience to identify and explore the essential components of peace processes. The book is organized around five key themes in peacemaking: planning for peace; negotiations; violence on peace processes; peace accords; and peace accord implementation and post-war reconstruction. .